Pancreas exocrine replacement therapy is associated with increased survival following pancreatoduodenectomy for periampullary malignancy. Issue 10 (October 2017) - Roberts, Keith J.; Schrem, Harald; Hodson, James; Angelico, Roberta; Dasari, Bobby V.M.; Coldham, Chris A.; Marudanayagam, Ravi; Sutcliffe, Robert P.; Muiesan, Paolo; Isaac, John; Mirza, Darius F.
Abstract: Background: Although many patients undergoing pancreatoduodenectomy (PD) for cancer have pancreatic exocrine insufficiency, pancreatic enzyme replacement therapy (PERT) is not routinely used, and effects upon post-operative survival are unclear. Methods: This review of patients undergoing PD for periampullary malignancy sought to test for an association between PERT and overall survival, with post-hoc subgroup analysis performed after stratifying patients by the year of surgery, pancreatic duct width and tumour type. Results: Some 202/469 (43.1%) patients received PERT. After accounting for pathological variables and chemotherapy, PERT use was found to be independently associated with improved survival on multivariable analysis [HR 0.72 (95% CI: 0.52–0.99), p = 0.044] and on propensity matched analysis (p = 0.009). The effect of PERT upon improved survival was predominantly observed amongst patients with a dilated pancreatic duct (≥3 mm). Discussion: PERT use was independently associated with improved survival following PD for cancer. The validity of this observation is supported by an effect largely confined to those patients with a dilated pancreatic duct. The nutritional status of patients undergoing PD for cancer needs further investigation and the effects of PERT require verification in further clinical studies.